Nearly spherical CoP nanoparticle/carbon nanosheet hybrids: a high-performance trifunctional electrocatalyst for oxygen reduction and water splitting. Issue 68 (4th December 2019) - Zou, Wenjian; Dou, Kunpeng; Jiang, Qi; Xiang, Jiadong; Kaun, Chao-Cheng; Tang, Hao
Abstract : The CoP nanoparticles/carbon sheets hybrid structures are highly efficient trifunctional electrocatalytic activities toward the oxygen reduction reaction, oxygen evolution reaction, and hydrogen evolution reaction under alkaline condition. Abstract : Developing active multifunctional electrocatalysts composed of earth-abundant and cheap elements is an urgent demand in energy conversion applications. This study presents a facile approach for the scalable synthesis of nanostructured cobalt phosphide embedded in carbon nanosheets (CoP NPs/CNSs). The hybrid structures show highly efficient trifunctional electrocatalytic activities toward the oxygen reduction reaction (ORR), oxygen evolution reaction (OER), and hydrogen evolution reaction (HER) under alkaline condition. The catalytic performances, which are remarkably superior to those of the previously reported CoP nanostructures enclosed by single or a few low index facets, can be attributed to the nearly spherical shape of the CoP nanoparticles with many more exposed crystal planes. Density functional theory (DFT) computations are performed to investigate the facet effects of CoP on electrocatalytic activity, and they reveal the relatively low overpotentials of (101) facets towards the OER and the free energy of water dissociation (Δ G H2 O ) and adsorbed H intermediates (Δ G H* ) of (311) toward the HER being close to thermoneutral. This work is expected to inspire the design and fabrication of multifunctional and high-efficiency electrocatalysts by selectively exposing specific crystal planes.